Why is advance care planning underused in oncology settings? A systematic overview of reviews to identify the benefits, barriers, enablers, and interventions to improve uptake - Guccione, Lisa; Fullerton, Sonia; Gough, Karla; Hyatt, Amelia; Tew, Michelle; Aranda, Sanchia; Francis, Jill (Frontiers in Oncology, 2023)
Background Advance care planning (ACP) centres on supporting people to define and discuss their individual goals and preferences for future medical care, and to record and review these as appropriate. Despite recommendations from guidelines, rates of documentation for people with cancer are considerably low. Aim To systematically clarify and consolidate the evidence base of ACP in cancer care by exploring how it is defined; identifying benefits, and known barriers and enablers across patient, clinical and healthcare services levels; as well as interventions that improve advance care planning and are their effectiveness. Methods A systematic overview of reviews was conducted and was prospectively registered on PROSPERO. PubMed, Medline, PsycInfo, CINAHL, and EMBASE were searched for review related to ACP in cancer. Content analysis and narrative synthesis were used for data analysis. The Theoretical Domains Framework (TDF) was used to code barriers and enablers of ACP as well as the implied barriers targeted by each of the interventions. Results Eighteen reviews met the inclusion criteria. Definitions were inconsistent across reviews that defined ACP (n=16). Proposed benefits identified in 15/18 reviews were rarely empirically supported. Interventions reported in seven reviews tended to target the patient, even though more barriers were associated with healthcare providers (n=40 versus n=60, respectively). Conclusion To improve ACP uptake in oncology settings; the definition should include key categories that clarify the utility and benefits. Interventions need to target healthcare providers and empirically identified barriers to be most effective in improving uptake. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?, identifier CRD42021288825.